Growth with Equity: Income Inequality in Vietnam, 2002–14 - Dwayne Benjamin; Loren Brandt; Brian McCaig (Institute for the Study of Labor (IZA), 2016)
We use the 2002 through 2014 Vietnam Household Living Standards Surveys to construct comparable measures of household income and estimates of income inequality over this high-growth period. We focus on two questions: How have benefits from growth been distributed; and do changes in the structure of the economy map into changes in inequality? We explore dimensions in which inequality may vary, notably urban versus rural, and by ethnic status. We also decompose inequality by income source to highlight key factors underlying the relatively low levels of inequality during this period. We find that agricultural opportunities played an important role in dampening inequality, but more important has been the steady development of wage-labor markets in both urban and rural areas. An important caveat to the generally rosy picture we paint is the deteriorating position of ethnic minorities. Finally, we draw comparisons with China and document key differences in their growth-inequality experience.
Keywords: D31; D63; O53; 330; Vietnam; income inequality; decomposition